2007
DOI: 10.1007/s00128-007-9180-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Biomonitoring of the Mzamza Population Exposed to Untreated Wastewaters

Abstract: A cytogenetic biomonitoring study was performed on people from the Mzamza community near Settat, Morocco. These subjects live in and near the Bou Moussa valley where wastewaters from a great number of industries are discharged without any treatment. This wastewater is used as a source of drinking water for their cattle and irrigation of their land. The Mzamza population is therefore presumably exposed to continuous low doses of different kinds of pollutants. Our study demonstrated significant increases in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…When the micronucleus frequencies were compared between control (tap water) and exposed cultures (waste and well water), statistically signifi cant increases were found for both stations and wells 21 and 46. Micronucleus frequency in the control culture was 3 micronuclei per 1000 binucleated cells, which is in accordance with literature and our own historical data (5,18). This frequency (and an absence of the doseeffect relationship) was also found for well 9 water, which was the most distant from the Boumoussa valley (both graph lines on Figure 2 are overlapping).…”
Section: Micronucleus Test and Proliferation Index (Pi)supporting
confidence: 90%
See 1 more Smart Citation
“…When the micronucleus frequencies were compared between control (tap water) and exposed cultures (waste and well water), statistically signifi cant increases were found for both stations and wells 21 and 46. Micronucleus frequency in the control culture was 3 micronuclei per 1000 binucleated cells, which is in accordance with literature and our own historical data (5,18). This frequency (and an absence of the doseeffect relationship) was also found for well 9 water, which was the most distant from the Boumoussa valley (both graph lines on Figure 2 are overlapping).…”
Section: Micronucleus Test and Proliferation Index (Pi)supporting
confidence: 90%
“…Of particular reference to our study is the study by Kholtei, who demonstrated a signifi cant increase in DNA breaks in cells exposed to wastewater from the town of Settat (2). Other investigations have confirmed genotoxic effects in humans (18) and animals (24) who drank the Boumoussa water and showed elevated micronucleus frequencies in their white blood cells. So far, no follow up is available on the health status of the investigated animals and humans, but these studies clearly suggest that their health may be impaired in the long run.…”
Section: Micronucleus Test and Proliferation Index (Pi)mentioning
confidence: 82%